Administration and Consultation of the Prophetic Era: A Study in the Context of Modern Times - Barvi, Muhammad Ramzan Najm (Journal of Islamic and Religious Studies, 2020)
The role of consultation in the success of the organization of a state. It is a source of the beauty of a democratic state. Consultation has an important place in every stable state. Allah Almighty has commanded his last Holy Prophet ﷺ for consultation in the Holy Quran, with his companions like other Prophets. The Holy Prophet ﷺ always ran his important affairs of state after laking opinions with his companions. He cleared the importance by his sayings and act. All modern democratic States should gain practical guidance from the Prophet Seerah. Giving importance to the opinion of the people’s representatives and making decisions in the light of their opinions reduces the gap between the government and the people and this is vital for an organized state.